Scent-based color identification for patients with visual disability - Flórez Fernández, Hector Arturo (Visión electrónica, 2014)
Nowadays, human disabilities are very common in all places around the world. However, when one person has a disability affecting one of the senses (e.g., sight, hearing), that person usually increases his/her capabilities with other senses. For instance, people with sight-associated disability normally increase their acuteness in senses like hearing and smell. Taking advantage of this human characteristic, in this paper we propose a prototype to offer patients with sight disability the opportunity to identify a set of colors using small amounts of particular essence.